SOLITON SOLUTIONS OF HIROTA EQUATION AND HIROTA-MACCARI SYSTEM BY THE (m +1/ G?)-EXPANSION METHOD - Bulut, Hasan; Akkilic, Ayse Nur; Khalid, Ban Jamal (Jomard Publishing, 2021)
In this paper, the (m +1/ G?)-expansion method is presented to seek the exact wave solutions of some nonlinear partial differential equations (NLPDEs), namely, the Hirota equation and the Hirota-Maccari system. The obtained solutions are solitary, topological, singular solitons and exponential function solutions. The 3D and 2D surfaces are also plotted for obtained solutions. This method is powerful, effective and it can be extended to many NLPDEs. © 2021, Jomard Publishing. All rights reserved.
Keywords: exact wave solutions; nonlinear partial differential equation; The (m +1/ G?)-expansion method; the Hirota equation; the Hirota-Maccari system